The Study of Shelf Operation for Advanced Osteoarthritis of the Hip - Nagai, Takafumi; Morita, Shinji; Nagatsuru, Yoshitaka; Namihira, Tatsukuni; Hirakawa, Shunichi (Orthopedics & Traumatology, 1990)
Thirty-seven patients (39 hips) with advanced osteoarthritis of the hip were treated by a shelf operation combined with valgus osteotomy. Their clinical and radiological results were evaluated by the JOA-score and acetabular head index (AHI). The average age at operation was forty-five years and six months old (range, 28 to 58 years). The mean follow-up period was two years and nine months (range, 1 to 5 years). The clinical result was good or excellent in seventeen hips (43.6%). The good and excellent group (over 80 points) in our clinical study was 84.6% for the AHI, while in the poor group (under 70 points) was 72.0%. It is apparent that a minimum of 85% coverage using the AHI is necessary for the best result.